First person - Danny Legge (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Danny Legge is first author on 'BCL-3 promotes a cancer stem cell phenotype by enhancing β-catenin signalling in colorectal tumour cells', published in DMM. Danny conducted the research described in this article while a PhD student in Professor Ann Williams's lab at Colorectal Tumour Biology Group, School of Cellular and Molecular Medicine, University of Bristol, UK. He is now a postdoc in the lab of Dr Keith Brown at Cancer Epigenetics Laboratory, School of Cellular and Molecular Medicine, University of Bristol, UK, investigating the role of cancer stem cells in colorectal cancer.